Analisa Kasus Penggelapan Dana Asuransi dan Divestasi Izin Operasi PT Wanaartha Life oleh OJK - Malik, Agusto Abdul; Usnan, Amar; Bestari, Qodri; Maryam, Salsabilla; Siswajanthy, Farahdinny (Interdisciplinary Explorations in Research Journal, 2025)
ABSTRACT Insurance comes from the Dutch word "verzekering" or "assurantie," which means insurer, that is, the party who bears the risk. Wanaartha Life's problems began to emerge along with the investigation into the PT Asuransi Jiwasraya (Persero) case. In the context of this investigation, the Attorney General's Office ordered the blocking of hundreds of securities accounts, including those belonging to Wanaartha Life. In this research, the author explains in detail the main causes of insurance fraud and the process by which it occurs, the impact of insurance fraud on public trust in the insurance industry, the financial consequences for customers and investors due to default, steps that can be taken to restore the reputation of insurance companies, the role of government and institutions supervisors in preventing insurance fraud, and legal protection provided to policyholders so that this case does not happen again in the future. Keywords : Insurance, fraud, customers and investors ABSTRAK Asuransi berasal dari kata Belanda "verzekering" atau "assurantie," yang berarti penanggung, yaitu pihak yang menanggung risiko. Permasalahan Wanaartha Life mulai mencuat seiring dengan penyidikan kasus PT Asuransi Jiwasraya (Persero). Dalam rangka penyidikan tersebut, Kejaksaan Agung memerintahkan pemblokiran ratusan rekening efek, termasuk milik Wanaartha Life. Dalam penelitian ini, penulis menjelaskan secara rinci penyebab utama penipuan asuransi dan prosesnya terjadinya, dampak penipuan asuransi terhadap kepercayaan masyarakat terhadap industri asuransi, konsekuensi finansial bagi nasabah dan investor akibat gagal bayar, langkah yang dapat diambil untuk memulihkan reputasi perusahaan asuransi, peran pemerintah dan lembaga pengawas dalam mencegah penipuan asuransi, dan perlindungan hukum yang diberikan kepada pemegang polis agar kasus ini tidak terjadi lagi di masa depan. Kata Kunci : Asuransi, penipuan, nasabah dan investor